What a Difference a Brick Makes? Transitions of Memory and Shanghai Shikumen Walls - Pawlik, Karolina (Śląskie Studia Polonistyczne, 2021)
This essay is intended as an appreciation of an overlooked element of Chinese material culture: discarded blue bricks from demolished shikumen houses in Shanghai. It contemplates the concept and materiality of a wall from a unique perspective, combining insights from Chinese architecture history and scholarly tradition of appreciating stones. Combining scientific and poetic approaches, the author argues that these bricks can be contemplated analogically to ink landscape paintings and famous Dali dreamstones. The author uses these clay objects as a starting point to reflect on the rapid transformation of Chinese cities and complex relationship between enduring tradition and ongoing modernization.